2021
DOI: 10.3390/pharmaceutics13020135
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Autophagy Induction by Lithium Decreases Neuroprotective Effects in the Striatum of Aged Rats

Abstract: The pharmacological modulation of autophagy is considered a promising neuroprotective strategy. While it has been postulated that lithium regulates this cellular process, the age-related effects have not been fully elucidated. Here, we evaluated lithium-mediated neuroprotective effects in young and aged striatum. After determining the optimal experimental conditions for inducing autophagy in loco with lithium carbonate (Li2CO3), we measured cell viability, reactive oxygen species (ROS) generation and oxygen co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Rapamycin, resveratrol, NAC and Mn-Tbap counteracted most of rotenone’s effects on OCR-parameters only after 72 h [ 11 ], possibly via different mechanisms, not necessarily related to their autophagy enhancement and/or ROS scavenging effects. Lithium-induced reversal of rotenone on OCR-parameters is compatible with the drug’s known positive effects on mitochondrial-function [ 75 77 ], possibly mediated via its effect on autophagy/mitophagy [ 75 , 78 ]. Indeed, Osete et al [ 76 ] recently reported amelioration of rotenone-induced mitochondrial respiration malfunction (measured as OCR) in iPSCs (induced pluripotent stem cells) derived neural precursor cells by lithium.…”
Section: Discussionmentioning
confidence: 79%
“…Rapamycin, resveratrol, NAC and Mn-Tbap counteracted most of rotenone’s effects on OCR-parameters only after 72 h [ 11 ], possibly via different mechanisms, not necessarily related to their autophagy enhancement and/or ROS scavenging effects. Lithium-induced reversal of rotenone on OCR-parameters is compatible with the drug’s known positive effects on mitochondrial-function [ 75 77 ], possibly mediated via its effect on autophagy/mitophagy [ 75 , 78 ]. Indeed, Osete et al [ 76 ] recently reported amelioration of rotenone-induced mitochondrial respiration malfunction (measured as OCR) in iPSCs (induced pluripotent stem cells) derived neural precursor cells by lithium.…”
Section: Discussionmentioning
confidence: 79%
“…However, Li 2 CO 3 increased basal oxygen consumption and decreased autophagic flow in the elderly striatum. Aged rats' striatums showed ultrastructural alterations, including lower amounts of normal mitochondria and lysosomes and electro-dense mitochondria with disorganized cristae [ 42 ]. As a result, the data indicate that, whereas older rats do not benefit from lithium-mediated neuroprotection, younger animals do.…”
Section: Reviewmentioning
confidence: 99%